Parametric analysis of analytical solutions of the rollover of precast beams on bearing pads - Oliveira,Marina Fernandes Alvarenga (2020)
abstract: Due to low stiffness to lateral bending, long prestressed precast concrete beams are subject to lateral instability. For this reason, the safety analysis of these beams during the transitory stages of transport, lifting and assembly is fundamental. This work presents a nonlinear analytical model for the parametrical analysis of beams on bearing pads in their definitive location, without the effective connections being made. Such a solution determines a critical load of instability and considers the geometry of the cross-section, physical characteristics of the materials as well as geometric imperfections. A parametrical simulation is performed for the initial eccentricity, the initial rotation of the beam, concrete resistance, bearing pads dimensions, and the cross-section of the beam. The results show that the parameters of most considerable influence on beam stability are rotation stiffness of the bearing and the geometric characteristics of the cross-section of the beam, which can result in a reduction of about 50% of the critical rollover load. In addition, the cracking load may, in some cases, be close to the critical toppling load.